“Evaluation of Effect of Amalaki Churna (Emblica Officinalis Gaertn.) As Rasayana and Its Free Radicals Scavenging Activity in Healthy Individuals on Basis of Time of Administration of Medicine” by Superoxide Dismutase Test (SOD) - T. Banne, Satej; S. Rao, Gundappa (International Journal of Psychosocial Rehabilitation, 2020)
The present study was carried out at Parul Institute of Ayurved, Parul University, Vadodara, Gujarat, India. Amalaki fruits were collected from Khanderao Market, Vadodara, Gujarat, India. The Amalaki fruit was authenticated at The Maharaja Sayajirao University of Baroda, Department of Botany, Faculty of Science, Vadodara-390 002, Gujarat, India, and the sample code number was compared with BARO 123450018408 and 18415. The main objective of the study is to screen a comparative study of Amalakichurna (Emblica officinalis Gaertn.) as Rasayana in three different Oushadhasevan kala, i.e., times of administration of medicine as Kinchitsuryodayajate (sunrise), Divas bhojane (midday meal), and Nishi (night meal), and regular food is given to the control group. Study design: A total of 100 healthy individuals were selected and divided into 4 groups. Control group: Regular food was given for 30 days Group 1: Amalaki churna was given for 30 days during Kinchit Suryodayajatesunrise process time (06:00 a.m.) Group 2: Amalaki churna was given for 30 days at Midday mealtime (12:00 pm) Group 3: Amalaki churna was given for 30 days at nighttime (08:00 p.m.) Superoxide dismutase was assayed in all the study groups by the method devised by Marklund S. and Marklund G., modified by Nandi and Chatterjee. Blood samples were collected from all the subjects. Analysis of the study was done by using Tukey’s multiple posthoc procedure and a one-way ANOVA test. Result: The serum SOD levels were significantly decreased in group 1 (8.09 units/ml) as compared to the control (14.37 units/ml), group 2 (9.74 units/ml), and group 3 (9.77 units/ml), respectively. Conclusion: These results provide enough evidence of increased oxidative stress and a compromised antioxidant defense system in groups of healthy individuals.